PENGEMBANGAN MEDIA BERBASIS CANVA DAN GENIALLY DENGAN MODEL ADDIE DALAM MATERI ANALISIS DATA DENGAN PENDEKATAN TEORI BELAJAR BRUNER PADA SEKOLAH DASAR - Melani Fitri Nurdiantiny; Azzahra Nurul Aini; Safira Pelita Herly Maesy; Alfiana Nurussama; Hafiziani Eka Putri (STKIP Subang, 2025)
This study was motivated by the need for engaging and interactive digital mathematics learning media to support the learning process of first grade elementary school students, particularly in data analysis topics. The study aimed to examine the validity and practicality of Canva- and Genially-based mathematics learning media developed using Bruner’s Learning Theory. The research employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The research subjects consisted of material experts, media experts, and first grade elementary school students. Data were collected using expert validation sheets and student response questionnaires. The results showed that the learning media achieved an average validity score of 92.56%, categorized as very valid, and a practicality score of 90.43%, categorized as very practical. These findings indicate that the developed media is feasible and can help support contextual, visual, and interactive mathematics learning. The implication of this study is the availability of digital learning media that facilitates teachers and students in the implementation of data analysis learning in elementary schools.